High frequency, spontaneous motA mutations in Campylobacter jejuni strain 81-176. - Krystle L Mohawk; Frédéric Poly; Jason W Sahl; David A Rasko; Patricia Guerry (PLoS ONE, 2014)
Campylobacter jejuni is an important cause of bacterial diarrhea worldwide. The pathogenesis of C. jejuni is poorly understood and complicated by phase variation of multiple surface structures including lipooligosaccharide, capsule, and flagellum. When C. jejuni strain 81-176 was plated on blood agar for single colonies, the presence of translucent, non-motile colonial variants was noted among the majority of opaque, motile colonies. High-throughput genomic sequencing of two flagellated translucent and two opaque variants as well as the parent strain revealed multiple genetic changes compared to the published genome. However, the only mutated open reading frame common between the two translucent variants and absent from the opaque variants and the parent was motA, encoding a flagellar motor protein. A total of 18 spontaneous motA mutations were found that mapped to four distinct sites in the gene, with only one class of mutation present in a phase variable region. This study exemplifies the mutative/adaptive properties of C. jejuni and demonstrates additional variability in C. jejuni beyond phase variation.